2012
DOI: 10.2527/jas.2010-3513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the administration program of 2 β-adrenergic agonists on growth performance and carcass and meat characteristics of feedlot ram lambs

Abstract: The aim of the study was to determine the effects of 3 feeding dose programs of the β-adrenergic agonists (β-AA) ractopamine hydrochloride (RH) or zilpaterol hydrochloride (ZH) for the final 30 d before slaughter on growth performance and carcass and meat characteristics of feedlot ram lambs. Eighty-four Dorper × Katahdin ram lambs (30.0 ± 1.6 kg) were blocked by BW and randomly assigned to pens (4 lambs per pen and 3 pens per treatment). Pens within a block were assigned randomly to 1 of 7 dietary treatments:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
4
5
3
Order By: Relevance
“…Improvement in growth rate has been the most consistent and DMI the least consistent effect of ZH on sheep. Contrary to the increased DMI observed in the present study, previous experiments have shown that ZH supplementation to finishing sheep have decreased DMI (López-Carlos et al 2011, 2012, or no effect on DMI (Estrada-Angulo et al 2008;Mondragón et al 2010;Avendaño-Reyes et al 2011). Although the reasons for inconsistencies of effects of ZH supplementation on DMI of finishing sheep are not certain, the responses have been associated to factors such as climatic conditions (Macías-Cruz et al 2013), initial BW (Aguilera-Soto et al 2008 and dose of ZH (López-Carlos et al 2011).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Improvement in growth rate has been the most consistent and DMI the least consistent effect of ZH on sheep. Contrary to the increased DMI observed in the present study, previous experiments have shown that ZH supplementation to finishing sheep have decreased DMI (López-Carlos et al 2011, 2012, or no effect on DMI (Estrada-Angulo et al 2008;Mondragón et al 2010;Avendaño-Reyes et al 2011). Although the reasons for inconsistencies of effects of ZH supplementation on DMI of finishing sheep are not certain, the responses have been associated to factors such as climatic conditions (Macías-Cruz et al 2013), initial BW (Aguilera-Soto et al 2008 and dose of ZH (López-Carlos et al 2011).…”
Section: Discussioncontrasting
confidence: 85%
“…slaughter has shown to consistently improve growth and feed efficiency in beef cattle (Avendaño-Reyes et al 2006;Lean et al 2014); however, it has been inconsistent in finishing lambs. Some studies have reported no effects (Macias-Cruz et al 2010;Dávila-Ramírez et al 2015), improvements of growth rate and feed efficiency without affecting DMI (Estrada-Angulo et al 2008;Mondragón et al 2010;Avendaño-Reyes et al 2011) or increased growth rate, and feed efficiency and decreased DMI (López-Carlos et al 2011, 2012 in sheep after 30-34 d consuming feedlot diets supplemented with ZH. Improvement in growth rate has been the most consistent and DMI the least consistent effect of ZH on sheep.…”
Section: Discussionmentioning
confidence: 99%
“…BUN has been suggested to indicate the relative rate of carcass protein accumulation (Chikhou et al, 1993). In the present work, BUN concentrations were decreased by clenbuterol hydrochloride and rBAR immunization and this agreed with the report of López-Carlos et al (2012), who found that serum urea N concentration of feedlot ram lambs was reduced by β-adrenergic agonist administration regardless of feeding programme period. The decrease in serum urea N concentrations observed in the present trial could be explained by the mode of action of clenbuterol hydrochloride and the antibodies, which promoted muscle protein synthesis and utilization of N.…”
Section: Blood Biochemical Parameterssupporting
confidence: 82%
“…In this study, lipid metabolites TC, HDL-C and LDL-C were unaffected by clenbuterol administration and rBAR immunization, which was in agreement with previous reports in beef cattle and sheep (López-Carlos et al, 2012). However, TC and LDL-C concentrations were decreased and HDL-C concentration was increased in healthy men by oral albuterol, a β 2 -selective adrenergic agonist.…”
Section: Blood Biochemical Parameterssupporting
confidence: 81%
“…In skeletal muscle, β2 adrenergic receptors are the most highly-expressed isoform, but β1 receptors and to a lesser extent β3 and α 1D receptors are also present [7, 8]. Growth studies in animals [9] have led to the development of isoform-specific β adrenergic growth promoters that are used as feed additives in the livestock industry to increase meat yield per animal [10]. In addition, reports show that β agonists are commonly used by athletes to boost muscle growth and athletic performance, despite being restricted by the World Anti-Doping Agency [11].…”
Section: Introductionmentioning
confidence: 99%